(untitled) (Altre Modernità, 2014)
Maria Canella, Sergio Giuntini, Marco Turinetto (eds.), Nonostante tutto. Sport e stile. 150 anni d’immagine al femminile (Ginevra-Milano, Skira, 2011, 224 pp. ISBN 8857-211-954)